Molecular Detection of the Seasonal Bacterial Diversity from a Freshwater Lake in West Bengal, India - Saha, Sanjib; Tripathy, Manoj Kr.; Dash, Gadadhar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Situated in the northeastern region of Kolkata, WB, Subhas Sarobar is a medium-sized artificial lake that is home to a variety of plants and animals, such as benthos, nekton, zooplankton, bacteria, and phytoplankton, all of which contribute to a balanced and interdependent ecosystem. The water's physic-chemical characteristics are impacted by seasonal variations in temperature, precipitation, and humidity, which could be a factor in the change in the population of fauna. In addition, this aquatic system uses wastewater from homes. Therefore, in addition to seasonal fluctuations, the physico-chemical properties of the lake water are impacted by domestic discharges, washing clothing and utensils, bathing, and disposal of plastic garbage near the water. All of these human activities eventually lead to a decline in the lake's water quality. The lake system's low DO and high nutrient content create an ideal habitat for the growth of bacteria, including those that are infectious and could harm public health and other aquatic species. Containing harmful bacteria species in water is dangerous and can lead to a number of health problems, including diarrhea and gastroenteritis with fever, chills, nausea, hypertensive septic shock, secondary lesions, and infection. It may be possible to successfully stop the spread of disease if the traits and specifics of pathogenic bacteria are understood. Several enteropathogenic bacteria, including Shigella, Vibrio, Cholera, Salmonella, Enterobacter, and Yersinia, were identified, isolated, and purified in this study. In a model of live and heat-killed mice, the spread of bacterial zoonotic infections to other animals was found to cause major public health issues for those who are directly or indirectly using this water.